Pengaruh Faktor-faktor Ekonomi Makro Terhadap Return Saham Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Perbankkan Peraih Indonesia Banking Award (IBA) Tahun 2018 - Zakiyah, Tuti (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2019)
This study aims to examine and analyze the direct effect of macroeconomic variables on stock returns, as well as the indirect influence of macroeconomic variables on stock returns through profitability as measured by ROA as an intervening variable. This research was conducted on banks that received the IBA 2018 award and were listed on the IDX for the period 2009-2017. The data used is quantitative secondary data obtained by documenting various official sites. In econometrics the research data is included in the panel data. The population in this study were 15 banks and obtained a sample of 10 banks for 9 years using a purposive sampling method to form a panel of 90 samples. Hypothesis testing in this study uses t-statistic test to determine the direct effect of independent variables and intervening variables on the dependent variable, and compare the value of direct influence and indirect influence to determine the indirect effect of independent variables on the dependent variable through intervening variables. The results of this study are that inflation does not have a direct influence on stock returns. The BI rate does not have a direct influence on stock returns. and changes in the money supply do not directly affect stock returns. Profitability has a significant positive direct effect on stock returns. Inflation has an indirect influence on stock returns through profitability as an intervening variable. The BI rate has an indirect influence on stock returns through profitability as an intervening variable. and the money supply has an indirect influence on stock returns through profitability as an intervening variable.